Factors related to the success in women's football–a systematic review - Wang, Sihang; Shen, Miao; Li, Pei; Liu, Hongyou (Frontiers in Sports and Active Living, 2025)
IntroductionFootball success is defined as the achievement of a team in the game, which is measured by the combination of winning championship, higher ranking and better performance. This study reviews the factors influencing the football success in women's football from macro (economy, politics, culture), meso (geographical environment, football tradition, talent development, gender equality, league prosperity), and micro (technical/tactical, physical performance, situational factors) perspectives.MethodsA systematic search was carried out in the Web of Science, Scopus, and Pub Med database, the search strategy included the terms for the population (“women” OR “female”), the sport (“football” OR “soccer”), the variables (determinant', “success”, “ranking”).ResultsA total of 62 studies were included in the analysis. The findings suggest that at the macro dimension, economic development positively correlates with FIFA rankings, and policy support influences football success. Culturally, a culture that emphasizes creativity and strength can facilitate the success in women's football, while a culture of conservatism and humility hinders it. Regarding meso factors, geographical and climatic conditions, football tradition, the quality of talent development, and the degree of gender equality also emerged as important determinants. At the micro dimension, factors such as scoring first, high-intensity running, ball possession, home advantage, and playing weaker teams are closely associated with match success.ConclusionThese insights offer evidence-based recommendations for policymakers to promote women's football through increased economic investment, infrastructure development, and prioritized support policies, while coaches are encouraged to optimize training processes and incorporate situational factors to enhance team performance.